2012
DOI: 10.1371/journal.pone.0051865
|View full text |Cite
|
Sign up to set email alerts
|

FSHD Myotubes with Different Phenotypes Exhibit Distinct Proteomes

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) is a progressive muscle disorder linked to a contraction of the D4Z4 repeat array in the 4q35 subtelomeric region. This deletion induces epigenetic modifications that affect the expression of several genes located in the vicinity. In each D4Z4 element, we identified the double homeobox 4 (DUX4) gene. DUX4 expresses a transcription factor that plays a major role in the development of FSHD through the initiation of a large gene dysregulation cascade that causes myoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
1
29
1
Order By: Relevance
“…Each culture presents a mix of either myotube phenotype in different proportions [65,66]. We selected two FSHD primary myoblast lines that were previously shown to mostly differentiate into myotubes with either the atrophic (aFSHD) or disorganized (dFSHD) phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each culture presents a mix of either myotube phenotype in different proportions [65,66]. We selected two FSHD primary myoblast lines that were previously shown to mostly differentiate into myotubes with either the atrophic (aFSHD) or disorganized (dFSHD) phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Primary human myoblasts were derived from muscle biopsies performed according to the current ethical and legislative rules of France, and written informed consent was obtained from all subjects, as directed by the ethical committee of the Centre Hospitalier Universitaire (CHU) Arnaud de Villeneuve (Montpellier, France) [65,66]. In addition, the use of this material was approved by the ethics committee of the University of Mons (ref # A901) and the ethics committee of ULB-Erasme (Brussels ref #B2011/003 and #P2015/516).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ret is expressed in the indirect flight muscles of Drosophila , and overexpression of constitutively active Ret (RET MEN2B ) in muscle via a MEF2-GAL4 driver causes increased muscle fibre size, irregular myofibrils and abnormal actin deposits (Klein et al, 2014). Interestingly, irregular myotube morphology is often reported in FSHD patient-derived cultures (Barro et al, 2010; Tassin et al, 2012). As we found that Ret was activated by DUX4 in murine satellite cells, it becomes a potential candidate for contributing to DUX4-induced myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of myoblasts from FSHD patients has revealed direct functional impairments, including increased susceptibility to oxidative stress (Winokur et al, 2003a, 2003b; Celegato et al, 2006; Macaione et al, 2007; Barro et al, 2010), up-regulation of apoptotic markers (Winokur et al, 2003a, 2003b; Sandri et al, 2001; Vanderplanck et al, 2011; Laoudj-Chenivesse et al, 2005) and repression of MYOD and MYOD-target genes (Winokur et al, 2003b; Celegato et al, 2006). Additionally, myogenic differentiation results in myotubes with either an atrophic, or hypertrophic and highly disorganised morphology (Barro et al, 2010; Vanderplanck et al, 2011; Tassin et al, 2012; Ansseau et al, 2009). Defects in myoblast function are likely to result in impaired muscle maintenance, directly contributing to clinical symptoms (Morgan and Zammit, 2010).…”
Section: Introductionmentioning
confidence: 99%